Analysis of Sustainable Development Goals (SDGs) 12 on the Environmental Performance of PT Pupuk Indonesia - Wahyu Aryanta, Dewa; Ketut Bayangkara, I. B. (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the 12th Sustainable Development Goals (SDGs) regarding consumption and production that are responsible for the environmental performance of PT Pupuk Indonesia (Persero). Using a descriptive qualitative approach and thematic analysis, data was collected from sustainability reports and official company documents. The results show that PT Pupuk Indonesia has integrated the principles of SDGs 12 into policies and operations, such as through ISO 14001 certification, Green and Gold PROPER ratings, decarbonization strategies towards Net Zero Emissions 2060, and 3R programs in waste management. The company also implements sustainability reporting based on GRI standards as a form of transparency and good governance. The research concluded that the company has taken tangible and progressive steps in supporting SDG12, although there is still room for strengthening sustainable strategies going forward.